2015
DOI: 10.1001/jamaoto.2014.3407
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tonsillectomy in the Treatment of Pediatric Autoimmune Neuropsychiatric Disorders Associated With Streptococcal Infections (PANDAS)

Abstract: This PANDAS cohort whose neuropsychiatric symptoms did not respond sufficiently to antibiotics may have gained benefit from tonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 15 publications
0
28
0
5
Order By: Relevance
“…Only 8 of 18 articles matched our search criteria and were eligible for further analysis [6], [10], [11], [12], [13], [14], [15], [16]. One article had been cited and was also included [17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 8 of 18 articles matched our search criteria and were eligible for further analysis [6], [10], [11], [12], [13], [14], [15], [16]. One article had been cited and was also included [17].…”
Section: Resultsmentioning
confidence: 99%
“…Complete therapeutic success was reported in 4 [6], [12], [14], [17] of the 8 single cases and in one case series [10] for further 3 patients. A benefit was not verified for the total of 82 patients who had undergone TE in the other two case series [11], [16], not even a positive tendency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of antibiotic treatment in PANDAS were also studied. Four studies without control groups found that antibiotics could be effective [118,120,129,133] (Table 5), although a study comparing azithromycin vs. placebo as a treatment for PANS over four weeks failed to find an effect of azithromycin on OCD symptoms as measured with the Children’s Yale–Brown Obsessive Compulsive Scale (CY-BOCS) [123] (Table 5). However, if streptococcal infection is still present during acute episodes of PANDAS, antibiotics are considered as the best treatment [167,168].…”
Section: Alternative Treatments For Ocdmentioning
confidence: 99%
“…PANDAS syndrome presents predominantly as an acute onset of OCD‐like symptoms. Other symptoms include ADHD (attention deficit and hyperactivity disorder)‐like behaviour, the child may be emotionally labile, may suffer separation anxiety, poor attention, ‘tic’ development and reduced visual–spatial capabilities . The diagnostic criteria were developed in 1998 by Swedo et al .…”
Section: Pandas Diagnostic Criteriamentioning
confidence: 99%